Process improvement of pharmaceutical grade ethanol production using sweet sorghum - Nadir, Najiah; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Mohd Yunus, Rosli (ILRAM Publisher, 2009)
The cooversion of s1arch to sugar can be achieved by hydrolysis process. The two-step enzymatic hydrolysis of sweet sorghum was performed by commercially available a-amylase and glucoamylase and further ethanol fermenlation of the obtained hydro1yzates by Saccharomyces cerevisiae was studied. In order to allain a higher ethanol yield, optimization study was carried out in the 2 litres stirred tmk bioreac1or, B-Braun bioreactor to investigate the effect ofmain factors of the hydrolysis process, namely, amount of substrale, temperature, time, and amount of enzyme for the maximum production of bioethanol. As shown in the analysis of variance (ANOVA) result, the amount of substrate, liquefilction and saccharification temperlIlUre have contributed more significant effect on hydrolysis process ofsweet sorghum.